Economic Entrepreneurship Skills in High School Students as a Pathway to Future Economic Growth - Tambengi, Wulan Mayasari (Newinera Publisher, 2023)
The subject of this research focuses on the impact of Economic entrepreneurship education in Indonesian high schools. Exploratory qualitative case studies were conducted and the data collection techniques included semi structured interviews, focus group discussion and documentation review. The study results indicate that knowledge-explicitness discrepancy in GAME and EIE courses curb entrepreneurial skills amongst students. The first student related challenge is that existing entrepreneurship education is seen as not applicable to their future career goals and thus requires contextually relevant solutions. The roles, responsibilities and relations of entities in schooling systems are highly legalistic, bureaucratic and hierarchical and limit teachers from practicing creativity. Implication of the results of this study are drawn in terms of emphasizing the value of experiential learning, topicality of entrepreneurship content in high schools of Indonesia, need to have flexible policies to improve the quality of teaching and learning of entrepreneurship in the high schools of Indonesia. Suggestions are made to create what is necessary in schools to help prepare children for future economic development.